ROC Working Party: Towards the Optimal Reserving Process. The Fast Close process. (3rd March 2015) - Bruce, Neil; Lauder, Alastair; Heath, Cameron; Bennett, Camilla; Wong, Chi; Overton, Gregory; Ryan, Joe; Laidlar, Katherine; Taylor, Keith; Jenkins, Tim
Abstract Our principal focus in this paper is on ways that a Fast Close process (or indeed any reserving process) can be structured to maximise the value added within the process given the time and resource available. This builds on the use of actual vs. expected techniques investigated in our previous paper, and also looks at forces external to the reserving function that may derail smooth progress. We highlight a number of practical ways that the balance can be restored in favour of adding value rather than crunching numbers. This paper forms the second in the TORP series.